Williams' nutrition for health, fitness & sport - Rawson, Eric S.; Branch, J. David 1956-; Stephenson, Tammy J.
"According to the World Health Organization, better health is the key to human happiness and well-being. Many factors influence one's health status, including some shared by various government and health agencies, such as safe living environments and access to proper health care. However, in general, one's personal health over the course of a lifetime is dependent more upon personal lifestyle choices, two of the most important being proper exercise and healthy eating. In the twenty-first century, our love affair with fitness and sports continues to grow. Worldwide, although rates of physical inactivity are still prevalent in developed nations, there are millions of children and adults who are active in physical activities such as bicycling, running, swimming, walking, and weight training. Improvements in health and fitness are major reasons more and more people initiate an exercise program, but many may also become more interested in sports competition, such as age-group road racing; running and walking race competitions have become increasingly popular, and every weekend numerous road races can be found within a short drive. Research has shown that adults who become physically active also may become more interested in other aspects of their lifestyles-particularly nutrition-that may affect their health in a positive way. Indeed, according to all major health organizations, proper exercise and a healthful diet are two of the most important lifestyle behaviors to help prevent chronic disease"--Provided by publisher.
CAC Camia (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Nutrition; Physical fitness; Sports -- Physiological aspects